PNET with neuroendocrine differentiation of the lung: Report of an unusual entity. (August 2014) - Barroca, Helena; Souto Moura, Conceição; Lopes, José Manuel; Lisboa, Susana; Teixeira, Manuel R.; Damasceno, Margarida; Bastos, Pedro; Sobrinho-Simões, Manuel
Ewing's sarcoma/primitive neuroectodermal tumor (PNET) has been the subject of recent reports describing morphologic variants (adamantinoma-like, large cell, spindle cell, sclerosing, clear cell, and vascular-like) of the most classic form, as well as cases displaying unusual morphologic differentiation and atypical immunohistochemical features. We report a case of an uncommon lung tumor in a 20-year-old female, morphologically and molecularly consistent with an Ewing's sarcoma/PNET tumor with foci of squamous differentiation, and peculiar expression of vimentin, high-molecular-weight keratins, p63, synaptophysin, and chromogranin. This case raises a challenging differential diagnostic problem with therapeutic implications: Should the patient be treated following the protocols for Ewing's sarcoma/PNET tumors or as for lung carcinoma with neuroendocrine features? The patient we report here was treated with neoadjuvant chemotherapy for Ewing's sarcoma/PNET according to Euro Ewing 99 study protocol followed by surgery and has no evidence of disease 15 months after the initial diagnosis. This highlights the importance of achieving the correct diagnosis of these atypical tumors using all clinical, morphological, and ancillary methods available to allow for their correct and timely treatment.